Health Security : A Need and Necessity For Senior Citizens In India - Raj kumar verma (Jai Maa Saraswati Gyandayini An International Multidisciplinary e-Journal, 2015)
In the present scenario it is said that health is everything because health is lost everything is lost. Health is one of the most important aspects for our lives. Suppose we are not healthy we can’t move a single step in our life and we can’t imagine of good or healthy life. We know that present condition is not good about the health standard in India. Even we can say that the general health standard of India is extremely bad. There is large number of children suffering from malnutrition. It is a very shame and if we talk about the youth and senior citizen’s condition it is also bad. As far as condition of youth is concerned there is many health insurance and other policies available for them but there is no health insurance and other policies available for senior citizens people. Now a day’s government does not pay attention to senior citizens health and there is no preventing measurements and not providing the proper treatment by the Government and other health societies, hospitals for senior citizens. We must know that Right to health is included directly in as a Fundamental Right in the Indian Constitution. The constitution framer imposed this duty on state to ensure social and economic justice. Part IVth the Constitution of India which are Direct Principles of State Policy imposed duty on States.